(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the research of this section, a study of the processes of obtaining stabilizing K-PAC-KMTs brands was carried out to drastically reduce the volume of shocks that occur in various subsurface layers during drilling.